Unpacking Cohort Social Ties: The Appropriateness of Perceived Social Capital to Graduate Early Career Performance in Construction Project Teams. Issue 4 (2nd October 2017) - Thomson, Derek S.; Carter, Kate; Grant, Fiona
ABSTRACT: Construction project teams require social capital. When present in appropriate forms, it creates the social cohesion through which individuals accept project goals as their own. It lets team members share knowledge when present and reveal when it is missing. In education, social learning helps students appreciate the need for social capital appropriate to team performance. In practice, social capital enables the project team learning that overcomes project-specific challenges. Despite this importance, little is known about how students perceive social capital or the compatibility of that understanding with construction project needs. To characterise this aspect of 'graduateness, ' collective understanding of social capital was elicited from construction students in a Scottish university by free recall. Analysis was structured around four dimensions of social capital: cohesion, legitimacy & authenticity, sharing, and safety. Notions of friendship were found to dominate student understanding of their social capital even though this understanding derived from settings where the need for capital to support team performance is emphasized. The potential for misalignment between the capital that graduating students bring into practice with that required by project teams was apparent. The case for further investigation of this influence on early career development was established.